1998
DOI: 10.1002/(sici)1096-9136(199804)15:4<327::aid-dia574>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

NEFA elevation during a hyperglycaemic clamp enhances insulin secretion

Abstract: Elevated non-esterified fatty acid (NEFA) levels may influence insulin secretion and contribute to the development of Type 2 DM. We investigated the effects of acute NEFA elevation in controls (n = 6) and subjects predisposed to Type 2 DM (n = 6) on basal insulin levels, and following glucose and arginine stimulation. Each subject had one study with a triglyceride (TG) plus heparin infusion (elevated NEFA levels) and another with normal saline. Twenty minutes after the TG or saline infusion began a glucose bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The prior increase of plasma NEFA concentrations resulted in higher plasma insulin concentrations during basal glucose and during glucose stimulation, with the first and second phase being exaggerated. Other studies also showed enhanced insulin secretion when plasma NEFA concentrations were increased for 20 min, 90 min or 5 h, by Intralipid and heparin in healthy volunteers [12,13,15]. A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The prior increase of plasma NEFA concentrations resulted in higher plasma insulin concentrations during basal glucose and during glucose stimulation, with the first and second phase being exaggerated. Other studies also showed enhanced insulin secretion when plasma NEFA concentrations were increased for 20 min, 90 min or 5 h, by Intralipid and heparin in healthy volunteers [12,13,15]. A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28].…”
Section: Discussionmentioning
confidence: 85%
“…Short-term in vitro incubation of islets with longchain fatty acids increased insulin release during glucose stimulation [10,11]. This was also seen in healthy volunteers after a short-term increase of plasma NEFA concentrations by Intralipid and heparin [12,13,14]. Contrary findings have been observed after a long-term increase of plasma NEFA concentrations.…”
mentioning
confidence: 81%
“…In that study, the shape of the C-peptide responses were virtually superimposable, suggesting that first and second phase were equally potentiated. An HGC study performed with and without preingestion of oral fat also concluded that firstand second-phase insulin release were equally potentiated (ϳ2-fold) (14), although a similar clamp study, in which the FFA level was elevated with an intravenous infusion of intralipid/heparin, showed that only the second phase was potentiated (17-25%) (27). Finally, a study comparing meal-induced insulin secretion with and without a concomitant intravenous glucagon-like peptide-1 infusion concluded that insulin secretion is augmented by glucagonlike peptide-1 in the absence of potentiation of the rateof-change component (K D ) (28).…”
Section: Discussionmentioning
confidence: 98%
“…Of the nutrient modulators, fatty acids are particularly important as, at one extreme, islet fatty acid deprivation essentially abolishes glucose-induced insulin secretion (GIIS) (4 -7), whereas at the other extreme, acutely elevated fatty acid levels augment GIIS (6,8,9). Elevated circulating free fatty acids (FFAs) most probably contribute to islet ␤-cell compensation in insulin-resistant states (10 -13) but if chronically elevated, particularly in association with high glucose (14), cause ␤-cell failure via diverse mechanisms including induction of ␤-cell apoptosis, reduced GIIS, and insulin biosynthesis resulting in type 2 diabetes (10 -16).…”
mentioning
confidence: 99%